Cytotoxicity and antifungal properties of hydroxychavicol against trichophyton rubrum - Ridzuan, P. M.; Mohamad, Nasir; Ismail, Salwani; Abdul Rahman, Nor Iza; Hamzah, Hairul Aini; Buyong, Zunariah; Mohd Hassan, Norazian; Baharudin, Roesnita (International Islamic University Malaysia, 2018)
Hydroxychavicol (HC) is a phenolic compound of betel leaf (Piper betle). It has been reported to have antifungal properties against dermatophytes including T. rubrum. The aim of this study was to identify the effects of the HC against T. rubrum. Broth dilution method was used to determine the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of the HC. Microscopic study of the treated fungus was done by transmission electron microscope (TEM). Cytotoxicity study using pre-adipocyte (3T3-L1) cell line was performed by means of MTT cell proliferation assay. The MIC and MFC results of the HC were both 0.49 µg/ml. Microscopic study revealed the destruction of the fungal cell wall and organelles. Cytotoxicity study showed HC to be non-toxic to the tested human cell line. In conclusion, HC may potentially be used as an alternative therapeutic agent against T. rubrum infections.